Optical and mechanical anisotropies of aligned electrospun nanofibers reinforced transparent PMMA nanocomposites. (November 2016) - Li, Biyun; Pan, Shengqiang; Yuan, Huihua; Zhang, Yanzhong
Abstract: This study aims to assess the nanofiber directionality effects on optomechanical properties of a widely used transparent thermoplastic poly(methyl methacrylate) (PMMA). Aligned fiber-hybrid mats consisted of nylon-6 (PA-6) nanofibers and PMMA microfibers are prepared using a self-blending co-electrospinning method, followed by hot press molding to fabricate into transparent nanocomposites. Effects of nanofiber orientation degree in two orthogonal directions and loading fraction on the optomechanical behavior of the nanocomposites are examined. Optical transmittance differences parallel and perpendicular to the nanofibers' orientation are found to vary in a range of 3.9–5.4% at 589 nm, and strong mechanical anisotropy is observed with the 1% PA-6/PMMA nanocomposites. A maximal of 3% PA-6 nanofiber loading maintains the nanocomposite high transmittance (>75%) with improved strength and toughness along the nanofiber axis. This study reveals evident anisotropic optomechanical properties of transparent nanocomposites, and highlights the great designability of transparent nanocomposites by using aligned nanofibers as the designing elements.